2022
DOI: 10.1002/ags3.12630
|View full text |Cite
|
Sign up to set email alerts
|

Changes in operative trends and short‐term outcomes of surgery for congenital biliary dilatation in adults using real‐world data: A multilevel analysis based on a nationwide administrative database in Japan

Abstract: Aim We aimed to evaluate the operative trends and compare the short‐term outcomes between open and laparoscopic surgery for congenital biliary dilatation (CBD) in adults using real‐world data from Japan. Methods Data from the Japanese Diagnosis Procedure Combination database on 941 patients undergoing surgery for CBD at 357 hospitals from April 1, 2016, to March 31, 2021, were analyzed. The patients were divided into two groups: open surgery (n = 764) and laparoscopic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Using the DPC database on 941 patients undergoing surgery for congenital biliary dilatation (CBD) at 357 hospitals, Mori et al have demonstrated that laparoscopic surgery (177 patients) for CBD had short‐term results comparable to those of open surgery (764 patients), while high cost of laparoscopic surgery is an issue that requires further research to solve (DOI:10.1002/ags3.12630). 3 By using DPC data and analyzing through PSM, Oba et al compared the efficacy and safety of mechanical bowel preparation (MBP, 1756 cases) alone and MBP combined with oral antibiotic bowel preparation (MOABP, 1756 cases) for rectal cancer surgery (DOI:10.1002/ags3.12641). 4 While there has been a trend to simplify preoperative preparation before colorectal surgery due to the prevalence of enhanced recovery after surgery program, this study has shown the “ real‐world ” information that MOABP for rectal surgery was associated with a decreased incidence of postoperative complications without increasing the incidence of Clostridium difficile colitis and methicillin‐resistant Staphylococcus aureus colitis (DOI:10.1002/ags3.12641).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Using the DPC database on 941 patients undergoing surgery for congenital biliary dilatation (CBD) at 357 hospitals, Mori et al have demonstrated that laparoscopic surgery (177 patients) for CBD had short‐term results comparable to those of open surgery (764 patients), while high cost of laparoscopic surgery is an issue that requires further research to solve (DOI:10.1002/ags3.12630). 3 By using DPC data and analyzing through PSM, Oba et al compared the efficacy and safety of mechanical bowel preparation (MBP, 1756 cases) alone and MBP combined with oral antibiotic bowel preparation (MOABP, 1756 cases) for rectal cancer surgery (DOI:10.1002/ags3.12641). 4 While there has been a trend to simplify preoperative preparation before colorectal surgery due to the prevalence of enhanced recovery after surgery program, this study has shown the “ real‐world ” information that MOABP for rectal surgery was associated with a decreased incidence of postoperative complications without increasing the incidence of Clostridium difficile colitis and methicillin‐resistant Staphylococcus aureus colitis (DOI:10.1002/ags3.12641).…”
mentioning
confidence: 99%
“…By extracting and examining the necessary information from “ big data ” of the DPC database, which is known as Japan's nationwide administrative database, we can truly see the current “ real‐world ” situation of the topic. Using the DPC database on 941 patients undergoing surgery for congenital biliary dilatation (CBD) at 357 hospitals, Mori et al have demonstrated that laparoscopic surgery (177 patients) for CBD had short‐term results comparable to those of open surgery (764 patients), while high cost of laparoscopic surgery is an issue that requires further research to solve (DOI:10.1002/ags3.12630) 3 . By using DPC data and analyzing through PSM, Oba et al compared the efficacy and safety of mechanical bowel preparation (MBP, 1756 cases) alone and MBP combined with oral antibiotic bowel preparation (MOABP, 1756 cases) for rectal cancer surgery (DOI:10.1002/ags3.12641) 4 .…”
mentioning
confidence: 99%